INFLUENCE OF ADJACENT AQUACULTURE ACTIVITIES ON SOIL PROPERTIES OF SANDY SOILS UNDER PADDY CULTIVATION IN GODAVARI DELTA. - T , USHA RANI (The Journal of Research ANGRAU, 2026)
Soil salinization of agricultural lands around aqua ponds due to seepage of water from ponds was studied in the year 2017-2020. The ponds selected were aqua ponds with sandy texture with and without any trench. Soil samples(50 no.) were collected from 0 meters (outer side of the pond or trench bund) up to 50meters distance from the pond and 10cm to 30 cm depth and analysed for pH, EC, Organic carbon, available Nitrogen, Phosphorous, Potassium, Sodium and TDS etc. The results indicated that pH and electrical conductivity decreased with increase in distance from the pond upto50 m distance from the pond. Available Nitrogen, Phosphorus and Potassium increased with distance from the aquapond with shrimp upto 50 m. Seepage is more in case of a pond without any trench when compared to a pond with trench. Salinization due to seepage was observed to a long distance in case of sandy soils.